Adaptive development of concomitant secondary mitral and tricuspid regurgitation after TAVR. (25th November 2020) - Winter, M.P; Bartko, P.E; Krickl, A; Gatterer, C; Nitsche, C; Koschutnik, M; Dona, C; Spinka, G; Siller-Matula, J; Lang, I; Mascherbauer, J; Hengstenberg, C; et al.
Abstract: Background: Concomitant secondary atrioventricular regurgitation is frequent in patients with severe aortic stenosis scheduled fortranscatheter aortic valve replacement (TAVR). The future implications of leaving associated valve lesions untreated after TAVR remain unknown. Aim of the present study wasto characterize the evolution of concomitant secondary atrioventricular regurgitations and to evaluate their impact on long-term prognosis. Methods: We prospectively enrolled 429 consecutive TAVR patients. All patients underwent comprehensive clinical, laboratory, and echocardiographic assessments prior to TAVR, at discharge, and yearly thereafter. All-cause mortality was chosen as primary study endpoint. Results: At baseline, severe concomitant secondary mitral regurgitation (sMR) was present in 54 (13%) and severe concomitant secondary tricuspid regurgitation (sTR) in 75 patients (17%). After TAVR 59% of patients with severe sMR at baseline experienced sMR regression, whereas analogously sTR regressed in 43% of patients with severe sTR at baseline. Persistence of sTR and sMR were associated with excess mortality after adjustment for our bootstrap-selected confounder model with an adjusted HR of 2.44 (95% CI 1.15–5.20, P=0.021) for sMR and of 2.09 (95% CI 1.20–3.66, P=0.01) for sTR (Figure 1). Furthermore patients showing regression of atrioventricular regurgitation exhibited survival rates indistinguishable to those seen in patients without concomitant atrioventricular regurgitation (sMR: P=0.83; sTR: P=0.74) Conclusion: Concomitant secondary atrioventricular regurgitation in patients with severe AS is a highly dynamic process with up to half of all patients showing regression of associated valvular regurgitation after TAVR and subsequent favorable post-interventional outcome. Persistent atrioventricular regurgitation is a major determinant of TAVR futility and proposes a window of early sequel intervention. Funding Acknowledgement: Type of funding source: None